2005
DOI: 10.1039/b504528b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical nanostructuring of fullerene films—spectroscopic evidence for C60 polymer formation and hydrogenation

Abstract: Electrochemical reduction of ordered C60 fullerene films in aqueous solution was studied by AFM, FTIR and Raman spectroscopy, mass spectrometry and elastic recoil detection analysis. During the irreversible reduction process the film morphology changed from a heteroepitaxial (111) surface to a nanostructured array with clusters of 20 to 50 nm lateral size on average. On the molecular level the initial C60 underwent electrochemical reactions to form C60 polymers and hydrogenated C60. Chemical follow-up reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…SEM image shows that the sizes of average diameter of the balls turn to be smaller and more homogeneous, and it is estimated to range from 0.277 ± 0.02 to 0.16 ± 0.01 lm, which indicates a structural rearrangement during the electrochemical scan. This is similar to that of C 60 films [38]. Upon reduction, chemical follow-up reactions of electrochemically formed anion with water attributed to the different reduction behavior of C 121 films in an aqueous solution compared to the reduction of C 121 films in organic solvents mentioned above.…”
Section: Electrochemistry Of C 121 /Gce In An Aqueous Solutionsupporting
confidence: 68%
“…SEM image shows that the sizes of average diameter of the balls turn to be smaller and more homogeneous, and it is estimated to range from 0.277 ± 0.02 to 0.16 ± 0.01 lm, which indicates a structural rearrangement during the electrochemical scan. This is similar to that of C 60 films [38]. Upon reduction, chemical follow-up reactions of electrochemically formed anion with water attributed to the different reduction behavior of C 121 films in an aqueous solution compared to the reduction of C 121 films in organic solvents mentioned above.…”
Section: Electrochemistry Of C 121 /Gce In An Aqueous Solutionsupporting
confidence: 68%
“…The much cited cation insertion mechanism has also been recently challenged by Dunsch and coworkers [23] who also found no evidence of cation insertion, and instead proposed a C 60 polymerization mechanism with concomitant protonation. Although the mechanism, as proposed by Dunsch et al is not charged balanced in their paper, it is not inconsistent with the results presented herein so far.…”
Section: Resultsmentioning
confidence: 97%
“…The attenuation of the A g (2) mode is apparent, along with the growth of orthorhombic polymer o ‐C 60 155. 156 In situ Raman spectroscopy has shown that both polymerization and hydrogenation of the fullerenes occur 156. On the other hand, in ionic liquids (cf.…”
Section: Spectroelectrochemistry Of Fullerenesmentioning
confidence: 99%
“…Section 4) the charged fullerenes react with the alkyl group of imidazolium cation 155. Furthermore, IR‐spectroscopy was used to study the chemical reaction products of the fullerene,156, 157 especially if the fullerene is used in thin layers together with organic polymers 158. 159 Therefore vibrational spectroscopy is a preferable technique in electrochemical studies of nanocarbon.…”
Section: Spectroelectrochemistry Of Fullerenesmentioning
confidence: 99%